Disposable Fox Ruler: a proposal to avoid cross-contamination - Mírian Galvão BUENO; Carolina Yoshi Campos SUGIO; Amanda Aparecida Maia Neves GARCIA; Simone SOARES; Karin Hermana NEPPELENBROEK (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Numerous pathogens, including SARS-CoV-2, can remain viable on surfaces over days, which favors cross-contamination. Preventive measures are essential to prevent infections and control the spread of COVID-19. Fox ruler is an essential device in the clinical planning of complete dentures and the contact with the patient's oral fluids during handling is unavoidable. Despite its importance, the conventional polycarbonate Fox ruler is easily damaged in the sterilization process. Therefore, the purpose of this article is to propose the use of a disposable Fox ruler. The confection is carried out in a simple way with wooden toothpicks joined by cyanoacrylate glue, following the same shape as the conventional one, but with the additional advantage of being made in an individual size according to the upper edge. The proposed disposable Fox ruler makes it possible to obtain the parallelism of the upper wax roller with the bipupillary line and with the Camper plane. Therefore, the disposable device described in this article was able to perform the same functions as the conventional one, in a practical way, without risks of cross contamination and with low cost.